Application of fenton oxidation for municipal sewage wastewater - Mohd Shafiq Md Zin (School of Bioprocess Engineering, University Malaysia Perlis, 2016)
Production of wastewater are become directly proportional increase every year. Development of human civilization with modern technology lifestyle cause of production of wastewater are become big challenges for the engineers. Conventional wastewater treatment are might be helpful in treating wastewater but the effectiveness are in low level of potential in treating wastewater in the future. This study was carried out to determine the best condition of Fenton oxidation in treating municipal sewage wastewater. Although this wastewater are being categorize as low strength of wastewater, this research might being able to describe the high effective of oxidation by controlling few important parameter. Removal of heavy metal (Pb) are being set as response variable to observe the efficiency in treating this wastewater. The optimization process were being tested by using Design Expert Software, in order to study the Response Surface Methodology (RSM). Central Composite Design were choosing in RSM study in order to get desired amount of catalyst and oxidant which give high removal of heavy metal. Maximum removal can be achieve (90.89%) when the sample was treated at pH 3 in the presence of hydrogen peroxide and iron of 443.24 mg/L and 16.08mg/L respectively. RSM are being choose as tools in optimizing process due to its ability to formulate, develop and analyse effect of model parameter.